Microtus (Microtus) levis Miller 1908 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Microtus (Microtus) levis Miller 1908 Microtus (Microtus) levis Miller 1908, Ann. Mag. Nat. Hist., ser. 8, 1: 197. Type Locality: Romania, Prahova, Gageni, in foothills of S Carpathian Mtns north of Bucharesti (after Ellerman and Morrison-Scott, 1951:698). Vernacular Names: East European Vole. Synonyms: Microtus (Microtus) caspicus Ognev 1950; Microtus (Microtus) epiroticus Ondrias 1966; Microtus (Microtus) ghalgai Krassovsky 1929; Microtus (Microtus) muhlisi Neuhäuser 1936; Microtus (Microtus) relictus Neuhäuser 1936; Microtus (Microtus) rhodopensis Heinrich 1936; Microtus (Microtus) rossiaemeridionalis Ognev 1924; Microtus (Microtus) subarvalis Meyer, Orlov, and Skholl 1972. Distribution: S Finland and Baltic region (Miljutin, 1997, 1998; Timm et al., 1998), eastwards through S Urals (Gileva et al., 1996) and Novosibirsk suburbs in W Siberia (Yakimenko and Kryukov, 1997) to SW margin of Lake Baikal, south through the Caucasus (Baskevich, 1996 b ) and probably NW Iran, and across the Ukraine in the north and Turkey in the south (Kryštufek and Vohralík, 2001) to E Slovakia (Mošanský, 1994), E and S Romania (Zima et al., 1981), Bulgaria, Greece, Macedonia and S Serbia and Montenegro (Petrov, 1992), and E Albania; accidentally introduced to the Arctic Svalbard Archipelago (Fredga et al., 1990; Yoccoz et al., 1993; as epiroticus ). Meyer et al. (1996) provide the best map. Conservation: IUCN – Lower Risk (lc) as Microtus rossiaemeridionalis . Discussion: Subgenus Microtus , arvalis species group (Pavlinov and Rossolimo, 1987, 1998; Pavlinov et al., 1995 a Zagorodnyuk, 1990). Populations referable to this E European species (2n = 54, FN = 56), first separated from M. arvalis by Meyer et al. (1972), have been listed or discussed as subarvalis (Corbet, 1978 c ), epiroticus (Petrov and Ruzic, 1982), or rossiaemeridionalis (Sokolov and Bashenina, 1994). Nomenclatural usage reviewed by Fredga (1995); Masing (1999) consolidated reports over the last 30 years spread under those epithets. The senior status of levis ...